Development of software for effective enterprice product policy creation - Lysytskyi, V. L.; Morhun, Ya. Yu. (НТУ "ХПІ", 2018)
The problem of developing a software tool for an effective enterprise product policy creation is considered. Existing methods for an enterprise product policy creation require the execution of a large number of computational operations, and those operations can be processed faster and more accurate by using of personal computers. The object of this research is IT-enterprise which is developing web-applications for automatization of relationships between enterprises and clients. The main point of the work is developing of program tool that uses algorithmic model of information technology for enterprise product policy creation to increase enterprise profitability. During the work, the current state of the problem of enterprise product policy creation, as well as existing software tools that could be used to create the enterprise product policy, were considered. A review of existing software development methodologies was performed. The task about developing of algorithmic model, software tool architecture and program system for enterprise product policy creation was set. The software tool that is developed contains of several functional modules. There are listed algorithms that describe how those modules work. The algorithmic model uses hierarchy analysis method for creation of assortment of product policy and simplex method for solving task of linear programming for calculation of production volumes for chosen products. The functional and non-functional requirements were developed for program, the three-layer software architecture of the web-application was chosen, program code was written, and program system was tested. The graphical user interface was developed and described. The graphical user interface provides users with ability to enter information, which is required for enterprise product policy creation, and retrieve results which are set of products, that enterprise should produce, and volumes of production of those products. The conclusion about results of developing program system and the possibility to use the algorithmic model in future researches were made. The results of the work can be used for development of information technology of enterprise product policy creation.

Розглядається проблема розробки програмного засобу для формування ефективної товарної політики підприємства. Існуючі методи формування товарної політики вимагають виконання великої кількості обчислювальних операцій, а використання електронно обчислювальних машин може збільшити швидкість і точність виконання таких операцій. Об’єктом дослідження є ІТ-підприємство, що здійснює розробку веб-додатків для автоматизації взаємодії між підприємствами та клієнтами. Метою даної роботи є розробка програмного засобу, який використовує алгоритмічну модель інформаційної технології формування товарної політики підприємства, для підвищення прибутковості підприємства. Під час виконання роботи, було розглянуто сучасний стан проблеми формування товарної політики підприємства, а також існуючі програмні засоби, що можуть бути використані для формування товарної політики підприємства. Було виконано огляд існуючих методів розробки програмних засобів. Поставлена задача розробити алгоритмічну модель, архітектуру програмної системи і програмну систему для формування товарної політики підприємства. Розроблений програмний засіб містить декілька функціональних модулів, алгоритми функціонування кожного модулю описані в цій статті. Алгоритмічна модель використовує метод аналізу ієрархії для формування товарного асортименту та симплекс-метод вирішення задачі лінійного програмування – для визначення об’ємів виробництва товарів. Для програмної системи були розроблені функціональні та нефункціональні вимоги, було обрано тришарову архітектуру веб-застосунку, написано програмний код і виконано тестування програмної системи. Розроблено графічний інтерфейс користувача, який надає можливість вводити інформацію, необхідну для формування товарної політики, та отримувати результати – товари, які необхідно виробляти, і об’єми виробництва таких товарів. Зроблено висновки про результати розробки програмного засобу і можливість використання алгоритмічної моделі в майбутніх дослідженнях. Результати роботи можуть бути використані як теоретичні основи для розробки інформаційної технології формування товарної політики підприємства.
Розробка програмного засобу формування ефективної товарної політики підприємства
Keywords: information technology; algorithmic model; hierarchy; optimization; software tools; інформаційна технологія; алгоритмічна модель; ієрархія